Analisis Perilaku Karyawan terhadap Perubahan Organisasi yang Dimoderasi oleh Dukungan Manajemen - Antika, Rindi; Gunarto, Muji (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The purpose of this study is to determine and analyse how employee behaviour in the face of organisational change is moderated by management support. This research understands how management support factors can moderate the relationship between employee change behaviour and its impact on the organisation The research design uses a quantitative approach through a survey. The unit of analysis in this research is employees and teaching staff at Bina Darma University with a total of 73 respondents. The data analysis technique was carried out with the SEM-PLS approach to test the hypothesis. The results of data analysis show that there is a negative influence between employee behaviour on organisational change of 0.188 and statistically significant because the t-count value is 1.318 (smaller than 1.96). There is a positive influence of management support on organisational change by (0.00). There is a weak moderating effect on organisational change with a value of 0.188. The managerial implications of this study can provide guidance for the management of private universities in improving management support, encouraging management to more actively communicate with employees during the organisational change process. It also underlines the importance of managerial training in dealing with organisational change and identifying barriers to change that may arise. The results of this study can also help the management team in developing a more effective change strategy, Bina Darma University can increase the level of em-ployee satisfaction and performance, and ultimately improve the overall efficiency of the organisation in the future